2012
DOI: 10.1111/j.1439-0531.2012.02123.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Association between PGF2α and Methyl 4‐hydroxybenzoate Sex Pheromone Prior to Electroejaculation in Dogs

Abstract: Electroejaculation is a technique that can be used to collect semen from canines, but its use with this group of animals is restricted by low success rate and low semen quality. Here, we evaluated whether pharmacological and sexual sensory stimuli, which may affect ejaculation, can increase electroejaculation efficiency and improve ejaculate quality. We worked with 20 dogs of mixed breed weighing between 5.3 and 22.2 kg, divided into two groups. Both groups were exposed to a spayed female for 10 min, but in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…However, Kruse and Howard (1983) in their study concluded that methyl p-hydroxybenzoate cannot be considered as a key sexual attractant for male dogs. Santos et al (2013), using methyl 4-hydroxybenzoate (cat. H5501; Sigma-Aldrich ® , Saint Louis, MO, USA) in their study also stated that "there was no sexual behavior observed between the dogs and the bitch (....), even though she was impregnated with artificial pheromone".…”
Section: Discussionmentioning
confidence: 99%
“…However, Kruse and Howard (1983) in their study concluded that methyl p-hydroxybenzoate cannot be considered as a key sexual attractant for male dogs. Santos et al (2013), using methyl 4-hydroxybenzoate (cat. H5501; Sigma-Aldrich ® , Saint Louis, MO, USA) in their study also stated that "there was no sexual behavior observed between the dogs and the bitch (....), even though she was impregnated with artificial pheromone".…”
Section: Discussionmentioning
confidence: 99%
“…However, analysis of the literature on the activity of methyl paraben in the context of sexual arousal shows a lack of efficiency of this substance (Kruse and Howard 1983, Tonosaki and Tucker 1985, Dzięcioł et al 2011. In the original article reporting an effective association between PGF2h and methyl 4-hydroxybenzoate prior to electroejaculation in dogs, while the authors obtained better results in a group of males exposed to methyl paraben, they also confirmed that there were no signs of sexual arousal observed in these males (Santos et al 2013). Also, while the influence of natural pheromones on physiological parameters (e.g., heart rate) in dogs was previously described by Dzięcioł et al (2012b), Santos et al (2013) did not find any differences between groups in heart and respiratory rate or rectal temperature.…”
Section: Discussionmentioning
confidence: 80%
“…In the original article reporting an effective association between PGF2h and methyl 4-hydroxybenzoate prior to electroejaculation in dogs, while the authors obtained better results in a group of males exposed to methyl paraben, they also confirmed that there were no signs of sexual arousal observed in these males (Santos et al 2013). Also, while the influence of natural pheromones on physiological parameters (e.g., heart rate) in dogs was previously described by Dzięcioł et al (2012b), Santos et al (2013) did not find any differences between groups in heart and respiratory rate or rectal temperature. In this case, a probable explanation for the better results obtained in males injected with PGF2α and stimulated by MP is the stimulating influence of PGF2α (Estienne and Harper 2000, Kozink et al 2002).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation